Design and Development of Aceclofenac Transdermal Therapeutic System: Influence of Chemical Permeation Enhancer on Drug Permeation Using Multiple Comparison Analysis - Chakraborty, Santanu; Kumar, Nitesh; Khandai, Madhusmruti; K. Ghosh, Ashoke (Drug Delivery Letters, 2015)
The objective behind this study is to prepare a transdermal therapeutic system for aceclofenac and ameliorate to evaluate the influence of chemical permeation enhancer (oleic acid) on drug permeation through the human cadaver skin. The influence of permeation enhancer on permeation flux (J), enhancement ratio of flux (ERflux) and permeability coefficient (Pss) was compared with the control batch (without permeation enhancer) by using one-way ANOVA followed by multiple comparison analysis. The drug permeation from the formulations was best characterized by Higuchi diffusion followed by case II to super case II transport mechanism. The optimized patch containing 5% w/w concentration of permeation enhancer was able to increase more than fivefold of drug permeation. Skin irritation studies suggest that optimized transdermal patch is non-irritating and safe for dermal application. Scanning electron microscopy, differential scanning calorimetry and X-ray diffraction studies confirmed the amorphous state of aceclofenac in the transdermal patch. So it is concluded from the above research that the prepared transdermal therapeutic system was dermatologically safe and able to deliver effective amount of aceclofenac through the transdermal route.
Keywords: activation energy